The Acuity and Manipulability of the ANS Have Separable Influences on Preschoolers’ Symbolic Math Achievement - Starr, Ariel; Tomlinson, Rachel C.; Brannon, Elizabeth M. (Frontiers in Psychology, 2018)
The approximate number system (ANS) is widely considered to be a foundation for the acquisition of uniquely human symbolic numerical capabilities. However, the mechanism by which the ANS may support symbolic number representations and mathematical thought remains poorly understood. In the present study, we investigated two pathways by which the ANS may influence early math abilities: variability in the acuity of the ANS representations and children’s’ ability to manipulate ANS representations. We assessed the relation between four-year-old children’s performance on a nonsymbolic numerical comparison task, a nonsymbolic approximate addition task, and a standardized symbolic math assessment. Our results indicate that ANS acuity and ANS manipulability each contribute unique variance to preschooler’s early math achievement, and this result holds after controlling for both IQ and executive functions. These findings suggest that there are multiple routes by which the ANS influences math achievement. Therefore, interventions that target both the precision and manipulability of the ANS may prove to be more beneficial for improving symbolic math skills compared to interventions that target only one of these factors.